Effects of a Hot-Water Extract of Allium hookeri Roots on Bone Formation in Human Osteoblast-Like MG-63 Cells In Vitro and in Rats In Vivo - Park, Heajin; Jeong, Jaehoon; Hyun, Hanbit; Kim, Jihye; Kim, Haesung; Oh, Hyun Il; Choi, Jai Yeon; Hwang, Hye Seong; Oh, Doo Byung; Kim, Jae Il; Kim, Ha Hyung (Planta Medica, 2016)
Allium hookeri is a wild herb found mainly in the Himalayas, growing at altitudes of 1400–4200 m. A. hookeri is widely consumed as a vegetable and herbal medicine in Asia, but its effects on bone health have not been reported previously. This study investigated the effects of a hot-water extract of A. hookeri roots on bone formation. The hot-water extract significantly increased the proliferation of in vitro human osteoblast-like MG-63 cells and the stimulatory effects on osteoblast differentiation were noticeably greater for the hot-water extract than for daidzein (a positive control), as reflected by alkaline phosphatase activity, collagen content, and mineral deposition. Expression of the bone-remodeling marker osteocalcin production and bone microstructural parameters were significantly improved in Sprague-Dawley rats in vivo after oral treatment with the hot-water extract compared with their control (saline-administered) counterparts. The chemical compounds of the hot-water extract were characterized by liquid chromatography-mass spectrometry, and alliin, sinapic acid, and ferulic acid, which exert beneficial effects on bone health, were identified. These findings indicate that A. hookeri can be used as a natural resource for increasing bone formation. This is the first report of the anabolic effects of A. hookeri extracts on bone formation in vitro and in vivo.
Keywords: Allium hookeri; Liliaceae; bone formation; human osteoblast-like cell; osteocalcin; bone microstructure; chemical compound